Simulation of pedestrian evacuation in university canteen based on cellular automata - Li, Yongxing (2021)
In this study, we firstly build up an exit choice model to describe the pedestrians' exit choice behavior in a specific place, i.e., university canteens. The pedestrians are assumed to minimize their evacuation time in choosing exits by explicitly considering the estimated evacuation time and effects of pedestrians' destinations. In addition, the behavior of food tray return is also captured in the proposed route choice model for pedestrians. Fusing the exit choice model and the route choice model into a cellular automata (CA)-based pedestrian simulation model, we simulate the pedestrian evacuation process in university canteen and the results illustrate the effectiveness of the modeling framework in terms of describing the evacuation process in university canteens. Specifically, destination is identified as a key influence factor for pedestrian evacuation, and pedestrians tend to select the exit that is closer to their destinations. If it is required to return the food tray to designated spots before leaving the canteen, the evacuation efficiency is significantly reduced. The simulation result can also assist in determining the optimal number of tray-return spots if maximum evacuation efficient is to be achieved. In presence of the specific parameter settings and canteen layout in the case study example, it is recommended to deploy four tray-return spots in the university canteen.